Analisis Strategi Diferensiasi Produk dalam Meningkatkan Daya Saing Bank Syariah di Era Digital - Indah Raissa Qur`ani; Haryanti, Peni (Jurnal Bisnis, Ekonomi Syariah, dan Pajak, 2025)
The rapid development of digital technology demands that Islamic banks innovate to compete with conventional banks and digital financial institutions. This study aims to analyze the product differentiation strategies implemented by Islamic banks to increase competitiveness in the digital era. The research method used is a descriptive qualitative approach, with data collected through literature studies, interviews, and observations of Islamic banks' digital services. The results indicate that product differentiation strategies are implemented through the development of digital services based on Sharia principles, improving the quality of mobile banking services, and creating innovative products that meet the needs of millennials and digital natives. Furthermore, the application of the values of transparency, fairness, and sustainability serves as a competitive advantage that distinguishes Islamic banks from conventional competitors. In conclusion, the success of product differentiation in the digital era depends on the ability of Islamic banks to integrate technological innovation with Sharia values, thereby increasing customer trust and loyalty and strengthening their competitive position in the digital financial industry.